Type I Interferons as Stimulators of DC-Mediated Cross-Priming: Impact on Anti-Tumor Response - Schiavoni, Giovanna; Mattei, Fabrizio; Gabriele, Lucia (Frontiers in Immunology, 2013)
Induction of potent tumor-specific cytotoxic T-cell responses is a fundamental objective in anticancer therapeutic strategies. This event requires that antigen-presenting cells (APC) present tumor-associated antigens (Ag) on their MHC class-I molecule, in a process termed cross-presentation. Dendritic cells (DC) are particularly keen on this task and can induce the cross-priming of CD8+ T cells, when exposed to danger or inflammatory signals that stimulate their activation. Type I interferons (IFN-I), a family of long-known immunostimulatory cytokines, have been proven to produce optimal activation signal for DC-induced cross-priming. Recent in vitro and in vivo evidences have suggested that IFN-I -stimulated cross-priming by DC against tumor-associated Ag is a key mechanism for cancer immunosurveillance and may be usefully exploited to boost anti-tumor CD8+ T-cell responses. Here, we will review the cross-presentation properties of different DC subsets, with special focus on cell-associated and tumor Ag, and discuss how IFN-I can modify this function, with the aim of identifying more specific and effective strategies for improving anticancer responses.